Die Gans mit dem scharfen Blick Zusätzliche Bemerkungen zum Hintergrund des Schu?lervergleichs in pLansing 3, 5–8 - Bojowald, Stefan.
In this article, pLansing 3, 5–8, which belongs to the class of admonitions of students, is scrutinized anew. The teacher´s rebuke is adorned metaphorically by a comparison of the pupil with the Nile goose. The Nile goose is cast into considerably bad light. The present article attempts to verify or falsify the teacher´s statements. As the results will show, the bird has, at least in part, been discredited unjustly. The ornithological aspects will play another important role.